Práticas de controle gerencial e fomentos voltados à agricultura familiar: um framework teórico - Queiroz, Andre Felipe (2022)
The literature on agricultural organizations shows that management control practices are subject to factors such as government policies and actions. In turn, the correlation between public funding and management control practices in agricultural organizations still does not present a consensus among researchers. Considering that in Brazil, the government employs several public policies to help small producers, specifically related to family farming, this research investigates the mediating effect of managerial control practices in the relationship between receiving incentives and the performance of properties linked to family farming. , and proposes a theoretical framework on the subject. To reach the objective, a research with mixed methods was elaborated containing a sequential explanatory strategy. In the qualitative phase, interviews were carried out with family farmers, technical specialists, financial specialists, public agents and agronomists, and a content analysis technique was later used. The results made it possible to: (1) identify the management control practices used by family farmers; (2) develop a classification of the 10 types of incentives used in family farming; (3) propose performance indicators for family farming based on the perception of family/business evolution used through the patrimonial and productive evaluation of farmers; and (4) develop a collection instrument to capture management control practices, incentives received and measure performance in family farming. In the quantitative phase, a survey with 204 respondents made it possible: (a) to verify the existence of a positive correlation between public funding and the adoption of management control practices; (b) measure the interrelationships between the constructs “management control practices”, “fostering” and “performance”. The results indicate that the receipt of support impacts the increase in the performance of family farmers, however, this increase in performance occurs due to the positive correlation between incentives and management control practices, so that management control is a hidden factor responsible for more 48% of the amplification that occurs in performance. The research results suggest guidelines for the development of public policies (I): by means of a technical opinion, it is suggested the creation of norms that establish, as a counterpart to the receipt of incentives, the participation of family farmers in training on management control, such as courses technicians and workshops, which would enhance the relationship between promotion and management control practices, expanding the performance of these farmers; (II) the research indicates the creation of a financial institution for Mato Grosso do Sul, aiming to meet the particularities of family farming in the state; and (III) suggests a change in family farming legislation in Brazil.